Potential of Nickel (Ni) Phytoremediation of Adaptive Species on Revegetation Land, PT. Vale Indonesia (Tbk). Pomalaa Site Kolaka Regency - Faisal, Faisal Danu Tuheteru; Asrianti , Asrianti Arif; Fauzi , Fauzi Rajab (Forestry Department, University of Muhammadiyah Makassar, 2017)
This research aimed to determinate the type of adaptive plant and its potential of phytoremediations on nickel revegetation land, PT. Vale Indonesia Tbk. Pomalaa site Kolaka Regency. The research was carried out in March - October 2016, with stages of explation and identification of adaptive plant species as well as analysis of nicel leaves and soil content using HNO3 or HClO4 method and (AAS) Atomic Absorbtion Spectrophotometry test. 12 types of adaptive plants from 12 genera and 10 family. That grow naturally on nickel revegetation land PT. Vale Indonesia Tbk. site Pomalaa. Species from tree habitus thet freguently found, namely Gymnostoma sumatrana, Sarcotheca celebica, Parinaria corymbosa, Timonius celebicus, Weinnmania fraxinea, Alstonia macrophylla. Based on analysis result, there four species that was categorized as low acummulator Nepenthes maxima, Cheilanthes tenuifolia, Timonius celebicus, Sarcotheca celebica. The highest absorber is S. celebica with nickel content 595 mg/kg dry weight leaves. S. celebica potential to be developed as nickel phytoremedian.